Response of Light Intensity to the Carotenoid Content of Sea Grape Caulerpa sp. - Rina Rosnawati; Nunik Cokrowati; Nanda Dinarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Caulerpa sp. is a green alga that grows naturally in Indonesian waters. Caulerpa sp. grows in shallow seas with calm currents and attaches to coral substrates or sand substrates and rock fragments. In Indonesia, this alga is widely used as a food ingredient. Caulerpa sp. Contains lignan which is beneficial to human health, namely its ability to prevent the growth of cancer cells. This study aims to determine the difference in the number of carotenoids in Caulerpa sp. with different light intensities using controlled containers at the Laboratory of Fish Production and Reproduction, University of Mataram. The method used was experimental with a Randomized Block Design (RAK) with 30 days of maintenance. The results showed the growth of Caulerpa sp. highest in treatment D (3 light 3000 lux) with an average absolute growth of 80 g, specific growth of 0,92 %, stolon length of 6,4 cm, and the highest carotenoid content. The lowest growth value was in treatment A (1 light 500 lux) with an absolute growth value of 35 cm, specific growth of 0,44%, stolon length of 4,6 cm, formula length 2,6 carotenoid content of 0.15 mg/g.